Digital Design / Second Edition - Mano, Moshe Morris (Prentice Hall International, 1991)
Preface, Binary Systems, Boolean Algebra and Logic Gates, Simplification of Boolean Functions, Combinational Logic, MSI and PLD Components, Synchronous Sequential Logic, Registers and Counters and the Memory Unit, Algorithmic State Machines (ASM), Asynchronous Sequential Logic, Digital Integrated Circuits, Laboratory Experiments, Standard Graphic Symbols, Appendix: Answers to Selected Problems, Index.